EGFR-mutated lung adenocarcinomas from patients who progressed on EGFR-inhibitors show high engraftment rates in xenograft models. (July 2020) - Martins-Filho, Sebastiao N.; Weiss, Jessica; Pham, Nhu-An; Li, Quan; Cabanero, Michael; Fares, Aline; Stewart, Erin L.; Shi, Ruoshi; Patel, Devalben; Pal, Prodipto; McConnell, Judy; Bradbury, Penelope Ann; et al.
Highlights: PDX are useful for biological studies in cancer; engraftment may not be stochastic. The overall engraftment rate of EGFR -PDX from lung adenocarcinoma is low. Latency of EGFR-PDX generation render the models inadequate for avatar experiments. Sample selection for EGFR -PDX experiments should target specific clinical scenarios. Engraftment of metastases (100%) or after failure to EGFR-inhibitors (70%) is high. Abstract: Objective: Patient-derived xenografts (PDX) are useful preclinical models to study cancer biology and mechanisms of drug response/resistance, particularly in molecularly targetable tumors. However, PDX engraftment may not be stochastic. We investigated clinical, histological and molecular features associated with PDX engraftment in a large cohort of EGFR -mutated lung adenocarcinoma (LUAD). Material And Methods: Samples were collected by different methods from patients at various disease stages and phases of treatment. PDX engraftment was defined as an ability to passage tumors twice in NOD-SCID mice. Uni- and multivariate logistic regression evaluated factors associated with engraftment. Results: Among 138 EGFR -mutated LUAD implanted into NOD-SCID mice, the overall engraftment rate was only 10% (14/138). However, engraftment was significantly higher in specimens from surgical resections or core-needle biopsies collected from metastatic sites (5/5; 100%) or from patients who had progressed on EGFR -inhibitors (7/10; 70%). Engrafted tumors usually showed poor histological differentiation, a solid morphologic pattern, and presence of either EGFR T790 M and/or TP53 mutations. Conclusions: Population level analyses of mutant EGFR -PDX show that these models might not fully recapitulate the inter-patient heterogeneity of EGFR -LUAD. However, mutant EGFR -PDXs may be useful to address key clinical questions, notably development of resistance to EGFR -inhibitors and disease progression to distant metastases.